Reoperations in the Secondary hyperparathyroidism - Morelli, Raúl; Santandreu, J; Vitancurt, Gustavo; Alvarez, Carmelo (Cirugía del Uruguay, 1996)
Primary hyperparathyroidism is present in most renal patients on cronic hemodyalisis. Surgery is indicated in cases not responding to medical treatment. Recurrence is always possible, as renal failure remains.ón A revision on the short bybliograpy is realized and, on 32 patients operated for secundary hyperparathyroidism, two cases reoperated for persistence and two cases reoperated for recurrence are reported.